Youth culture and the media : global perspectives - Osgerby, Bill (Abingdon ; New York : Routledge, 2020)
"This expansive, lively introduction charts the connections between international youth cultures and the development of global media and communication. From 1950s drive-ins and jukeboxes to contemporary social media, the book examines modern youth cultures in their social, economic and political contexts. Exploring the rise of young people as a distinct media market, the book examines the relation of youth to modern consumerism, marketing and digital technologies. The chapters are packed with analysis of media representations of youth, debates about the media's 'effects' on young audiences, and young people's use of the media to elaborate identities and negotiate social relationships. Drawing on a wealth of international examples, the book explores the impact of globalisation and new media technologies on youth cultures around the world. Assessing a profusion of worldwide research, the book shows how modern youth cultures can only be understood as part of an international web of connections, exchanges and experiences. With an ideal balance between detailed examples and engaging analysis, this book is a must-read for anyone interested in youth cultures and the modern media"--
OCLC-licensed vendor bibliographic record.
Keywords: Youth -- Social aspects; Mass media and youth; SOCIAL SCIENCE / Media Studies